Menonton Kartun Bagi Remaja: Peran Video Animasi Terhadap Agresi di Kalangan Siswa Sekolah Menengah Atas - Zaini, Desmaniarti; Fatah, Vera Fauziah; Meilianingsih, Lia; Putri, Tri Antika Rizki Kusuma (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Aggressive behavior among secondary school students, including bullying and acts of revenge, constitutes a significant public health concern, particularly in Indonesia. Despite various interventions implemented by schools and families, aggressive tendencies persist, with many adolescents continuing to engage in physical violence. Objective: This study aimed to examine the effectiveness of animated video media in reducing aggressive behavior among secondary school students in Bandung City, Indonesia. Methods: This pre-experimental study involved 208 secondary school students in Bandung City, Indonesia. Participants were assigned to either an intervention group (n = 104) or a control group (n = 104). The intervention group viewed a 30-minute animated educational video each day for seven consecutive days, focusing on understanding and managing aggression. Levels of aggression were assessed using the Buss–Perry Aggression Questionnaire through pre-test and post-test evaluations. Results: The findings revealed a statistically significant reduction in aggression levels among participants in the intervention group (p < 0.001), whereas the control group exhibited no significant change (p = 0.648). Hostility and retaliatory thoughts were more prevalent among younger adolescents. Regression analysis identified age, physical aggression, and anger as significant predictors of total aggression. Conclusion: The study underscores the potential of animated educational media as an engaging and developmentally appropriate intervention for preventing aggressive behavior in the digital era. The integration of multimedia-based learning into school health programs aimed at improving emotional regulation and conflict resolution skills may serve as an effective strategy to mitigate aggression among adolescents.